Local Government: Constitutional Vision and Present Practice (Research Nepal Journal of Development Studies, 2019)
Is it local government or local level unit of provincial and federal level governments? The constitution is still unclear. The constitution has not any provision of opposition party but it has executive, legislative and judiciary power allocation system of the organs of a government. To explore the vision and practice of local governance in Nepal, the study has been conducted. The methodology consists of analyzing primary and secondary sources. Primary data have been collected through field discussions with the stakeholders. Regarding the local governance various recommendations are presented in conclusion.